Design of the inverter in high accuracy and development of work therein by using compound ligation - Baqir, Muhammed Hussein; Haziq, Nor Mohd; Wahab, Noor Izzri Abdul (Eastern-European Journal of Enterprise Technologies, 2022)
A ligation (CL) system with a very high frequency in an inverter was used, it is a novelty in this study. We also employed a three-phase dynamic load (positive sequence voltage) to correct the power factor and account for active and reactive power in the output system this work is a novelty. The technique through compound ligation (CL) can improve inverter output waveform by reducing losses caused by ingrained agents in voltage source inverters (VSI), such as dead time caused by overload or voltage drop in an inverter's output, or abnormal load current conditions such as a short circuit current occur in the output stage of the inverter, and so on. The invention relates to the conversion of D.C. to A.C. power inverters, it is preferable to use compound ligation to achieve high efficiency, the device is lightweight, and has low losses and good precision. In addition, the present invention relates to improving an inverter load request sensation circuit, smoothing operational current, inverter response, and inverter spontaneous power factor improvement, as well as correction of the reactive power of passive components. In addition, an inverter with high active power (P) equal to (2.6×106 Watt), reactive power (Q) (5.4×107 VAR), was designed, and used positive sequence voltage (1.6×108 Watt ), as well as the switching period (10µs), The system's total harmonic distortion (THD) in voltage and current was 0.11 percent, while the system's accuracy was 99 percent. This is developed by using FPGA and oscillator circuit and programmable peripheral interface 8255 A as well as, ultrasonic PWM with a high-frequency range of (20–500 kHz) as demonstrated evidenced by the results obtained